2023
DOI: 10.1002/anie.202215933
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Harvesting of Multiple Hot Holes via Visible‐Light Excitation of Plasmonic Gold Nanospheres for Selective Oxidative Bond Scission of Olefins to Carbonyls

Abstract: Using visible photoexcitation of gold nanospheres we successfully demonstrate the simultaneous harvesting of plasmon-induced multiple hot holes in the complete oxidative scission of the C=C bond in styrene at room temperature to selectively form benzaldehyde and formaldehyde, which is a reaction that requires activation of multiple substrates. Our results reveal that, while extraction of hot holes becomes efficient for interband excitation, harvesting of multiple hot holes from the excited Au nanospheres becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, it has also been experimentally shown that a small number of h + are produced below the threshold of the intraband transition (600 nm), and above (>640 nm). [ 68 ] This correlated with the role of h + on visible light but posed a question on the apparition of holes in NIR. There is no experimental evidence of the generation of OH species on gold nanoparticles, [ 69 ] except under ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has also been experimentally shown that a small number of h + are produced below the threshold of the intraband transition (600 nm), and above (>640 nm). [ 68 ] This correlated with the role of h + on visible light but posed a question on the apparition of holes in NIR. There is no experimental evidence of the generation of OH species on gold nanoparticles, [ 69 ] except under ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Many kinds of chemical reactions caused by hot-electron transfer have been reported, following pioneering studies, including azo-bond formation, , epoxidation, and H 2 dissociation . In recent years, the generation and utilization of hot holes for chemical reactions have also attracted increasing attention. Recent studies have revealed that hot holes can enhance or induce various chemical reactions such as the oxidative dissolution of Au nanorods, azo coupling reaction of adenine, and oxidative scission of the CC bond, and so on.…”
Section: Diverse Excitation Sourcesmentioning
confidence: 99%
“…(a) Proposed mechanism for the plasmon-induced oxidative scission of styrene on Au nanospheres. Reproduced with permission from ref . Copyright 2023 John Wiley & Sons.…”
Section: Diverse Excitation Sourcesmentioning
confidence: 99%
“…13−25 However, most reported methods for this transformation rely on transitionmetal-based catalysts or require harsher reaction conditions or toxic oxidants. [13][14][15][16][17][19][20][21]26 Visible-light photoredox catalysis has emerged as a powerful tool for sustainable organic synthesis. 9,23,27,28 Initially, expensive transition-metal photocatalysts (such as Ir or Ru complexes) or photounstable organic dyes were often employed for catalytic conversions.…”
Section: ■ Introductionmentioning
confidence: 99%